2020
DOI: 10.1021/acsami.0c04340
|View full text |Cite
|
Sign up to set email alerts
|

Problem of Diminished cRGD Surface Activity and What Can Be Done about It

Abstract: RGD peptides play a pivotal role in growing and diverse areas of biological research, ranging from in vitro experiments probing fundamental molecular mechanisms of cell adhesion to more applied in vivo strategies in medical imaging and cancer therapeutics. To better understand the outcomes of RGD-based approaches, we quantified the degree to which cyclic RGD (cRGD) activity is blocked by nonspecific binding of commonly used medium constituents. First, we show that recombinant αVβ3 integrins can be used as a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Fig 4a-c shows the tracking of several MDA-MB-231 cells segmented via the self-supervised approach under 10X phase contrast microscopy on cRGD functionalized gold coverslips. 31 Fig 4a shows the labeled tracks of the cells’ centroids over the course of 400 minutes, with the corresponding initial and final image shown in Figs 4b,c. The cell associated with track 2 undergoes mitosis at approximately 320 minutes, creating two new tracks (5 and 6) for the daughter cells.…”
Section: Resultsmentioning
confidence: 99%
“…Fig 4a-c shows the tracking of several MDA-MB-231 cells segmented via the self-supervised approach under 10X phase contrast microscopy on cRGD functionalized gold coverslips. 31 Fig 4a shows the labeled tracks of the cells’ centroids over the course of 400 minutes, with the corresponding initial and final image shown in Figs 4b,c. The cell associated with track 2 undergoes mitosis at approximately 320 minutes, creating two new tracks (5 and 6) for the daughter cells.…”
Section: Resultsmentioning
confidence: 99%
“…The surfaces and thiol design specifications defined the roughness, stiffness and tether length parameter space of the experiments: the surfaces are ultra smooth with an average surface roughness of 0.5 nm based on AFM characterization 30 ; the substrate stiffness is maximal due to direct conjugation of the cRGD peptide to the underlying Au/glass substrate (> 50 GPa versus ~ 1kPa -1MPa for most hydrogel constructs); the tether length, based on the constituent alkane and PEG linker lengths, is 3.8 nm which is categorized as short for PEG tether linker length studies that typically run from several nanometers to hundreds on nanometers 19,32 . As will be discussed in detail below, the surface activity was systematically varied by adjustments of the SPO:SPC ratio.…”
Section: Methodsmentioning
confidence: 99%
“…We emphasize the word active in this work because we have previously shown that RGD surface activity can be dramatically reduced by blocking from a variety of common media and surface functionalization components (e.g. serum, BSA and PLL-PEG), which in turn affects cell phenotype 30 . Thus, even when using sophisticated lithographic approaches, the active ligand density can vary with laboratory methodology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations